2004
DOI: 10.1104/pp.103.034900
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Auxin Transport and the Actin Cytoskeleton in Developmental Polarity ofFucus distichusEmbryos in Response to Light and Gravity

Abstract: Land plants orient their growth relative to light and gravity through complex mechanisms that require auxin redistribution. Embryos of brown algae use similar environmental stimuli to orient their developmental polarity. These studies of the brown algae Fucus distichus examined whether auxin and auxin transport are also required during polarization in early embryos and to orient growth in already developed tissues. These embryos polarize with the gravity vector in the absence of a light cue. The auxin, indole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 64 publications
0
47
0
1
Order By: Relevance
“…Genetic or pharmacological manipulation of PAT that disturbs the auxin maximum dramatically alters root patterning (1,31). Numerous pharmacological investigations have confirmed the close correlation between PAT and the actin cytoskeleton (11,(16)(17)(18). In Arabidopsis, auxin transport inhibitors like 2,3,5-triiodobenzoic acid induce bundling of actin filaments and inhibit endocytosis (15,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic or pharmacological manipulation of PAT that disturbs the auxin maximum dramatically alters root patterning (1,31). Numerous pharmacological investigations have confirmed the close correlation between PAT and the actin cytoskeleton (11,(16)(17)(18). In Arabidopsis, auxin transport inhibitors like 2,3,5-triiodobenzoic acid induce bundling of actin filaments and inhibit endocytosis (15,18).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the auxin IAA induces actin bundling in Arabidopsis thaliana root cells (15). Pharmacological studies suggest that the actin cytoskeleton partially affects the directional transport of auxin by modulating cycling of auxin efflux carriers (16,17). In Arabidopsis root cells, the actin inhibitor cytochalasin D inhibits brefeldin A (BFA)-mediated PIN1 internalization (11), whereas latrunculin B impairs the polar localization of PIN1 in protophloem cells (18).…”
mentioning
confidence: 99%
“…Recent studies revealed the important roles of the actin cytoskeleton in auxin transport and related growth (Geldner et al, 2001;Friml et al, 2002). Treatment with latrunculin B, an inhibitor of actin filament assembly, may enhance gravitropism through the alteration of auxin transport Sun et al, 2004). The formation of cortical F-actin in Arabidopsis seedlings in turn is controlled by ROP (for Rho-of-plant) GTPases , and actin-depolymerizing factor mediates RAC/ROP GTPase-regulated pollen tube growth (Chen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Given its large size and its ease of manipulation, the Fucales zygote has been particularly amenable to cytological and pharmacological experiments (Kropf, 1997). Polarization of the zygote after fertilization involves several subcellular components (cell wall, microtubules, centrioles, and actin; for review, see Kropf, 1992) and is affected by auxin, which alters the polarity of the embryo and its developmental pattern (Basu et al, 2002;Sun et al, 2004). However, Fucus is not amenable to genetic studies, limiting its utility in further investigations of the processes controlling morphogenesis in brown algae.…”
mentioning
confidence: 99%